SAT0385 Multiple infection is independently related to death in adult patients with hemophagocytic syndrome: etiopathogenically-driven multivariate analysis in 151 patients. (12th June 2018) - Retamozo, S.; Brito-Zerón, P.; Kostov, B.; Moral-Moral, P.; Martínez-Zapico, A.; Díaz-Pedroche, C.; Fraile, G.; Pérez-Guerrero, P.; Fonseca, E.; Robles, A.; Vaquero-Herrero, M.; Calvo, M.A.; et al.
Abstract : Objectives: To characterise the etiologies and clinical features at diagnosis of patients with hemophagocytic lymphohistiocytosis (HLH) and correlate these baseline features with survival using an etiopathogenically-guided multivariate model. Methods: The HLH Study Group of the Spanish Group of Autoimmune Diseases (GEAS) was formed in 2013 with the aim of collecting a large series of Spanish adult patients with HLH with substantial experience in the management of patients with systemic diseases. By October 2017, the database included 151 consecutive patients who fulfilled at least 5 of the 8 criteria proposed by the Histiocytosis Society in 2004. Results: The cohort consisted of 151 patients (91 male, mean age 51.4 years). After a mean follow-up of 17 months, 80 (53%) patients died. With respect to the HLH-dependent variables, adenopathies (HR 0.63, p=0.040), low platelets (HR 3.39, p=0.008), leukopenia (HR 1.81, p=0.047), severe hyponatremia (HR 1.61, p=0.042), disseminated intravascular coagulation (HR 1.87, p=0.034), bacterial infection (HR 1.99, p=0.025), mixed microbiological infections (HR 3.42, p=0.008) and >1 infectious trigger (HR 2.95, p=0.003) were associated with death. Time-to-event analyses for death identified a worse survival curve for patients with neoplasia (p<0.001), mixed microbiological (p=0.019) and >1 (p=0.011) infections and glucocorticoid monotherapy (p=0.021). After adjusting for confounding variables, platelets<100, 000/mm3 (HR 2.64), severe hyponatremia (HR 1.88), >1 infectious trigger (HR 3.43) and mixed microbiological infection (HR 2.96) remained significant. Multivariate Cox proportional hazards regression analysis identified >1 infectious trigger (HR 2.60, 95% CI 1.16 to 5.84) as the only variable independently associated with death. Conclusions: The mortality rate of adult patients diagnosed with HLH exceeds 50%. Infection with >1 microbiological agent was the only independent variable associated with mortality irrespective of the underlying disease, epidemiological profile, clinical presentation and therapeutic management. Disclosure of Interest: None declared